(untitled) (Al-Academy, 2019)
The history of civilizations in the past centuries is a rich source for creativity and inspiration in all areas of art and design, especially in the field of fashion design. Many designers draw their designs from previous eras; which is the aim of this research as we propose designing fashion the mannequin for the category of young girls aged between (10-18). The costumes were inspired by Victorian women’s costumes during the time period (1860-1890) and were subdivided into three time periods (1860-1870), (1870-1880), (1880-1890) forming three designs for each time period , analyzing the nine designs to achieve the creative , functional and aesthetic aspects that are appropriate for the age group (research sample). The importance of the research lies in it being an analytical historical study. The implementation of the designs depends on the method of formation on the mannequin of the young age group, which makes it different from studies that always rely on the formation women mannequin. The pieces were referred by the faculty members of Umm Al-Qura University, the Department of Fashion Design. The results revealed that there are statistically significant differences between the nine designs in terms of the design elements, basis and principles of the design, functional, creative and aesthetic sides. Design number 4 met the design requirements with a percentage of 44.275; design number 2 met the principles of the design scoring 39.437%; design number 9 scored 53.037% in regards to practicality; design number 4 obtained 34.125 on the aspect of creativity and design number 9 accumulated 58.8% on the aesthetic side. The paper concludes with recommendations to conduct further studies that link the Draping method on the mannequins and the field of fashion history in different civilizations. Attention to the Draping of fashion on the mannequins for the category of young girls